Desenvolvimento e validação de um sistema eletromecânico para determinação do torque nas rodas motrizes de tratores agrícolas - Fiorese, Diego Augusto [UNESP] (2014)
The transmissions of agricultural tractors transfer the engine power to the drive wheels and the torque, available in the rotated, is converted into gross traction, which is responsible for overcoming the rolling resistance of the tractor and for the net traction on the drawbar. Based on these premises, this research aims to develop an electromechanical system, which we designate torque meter or torque transducer, to determine the torque and power on the axle of the driving wheels in agricultural tractors, and validate it through traction tests, with the support of a dynamometer car, and electronic instrumentation for data acquisition. The work was conducted at the Agro Forestry Machine and Tire Testing Center (NEMPA) at the College of Agronomic Sciences, São Paulo State University (FCA/UNESP), Botucatu-SP, Brazil. The torque meter was developed using specific software for mechanical design, and was built to be installed on rear axle of tractors of up to 90kW. The equipment was made with robust metal structure, able to withstand high demands of torque, and possible to be adapted to any tractor with similar features with equal or less power, simply by meeting the dimensional peculiarities of each model. The torque meter is based on a lever arm (torsional moment) from which it is obtained the strength values with a load cell and the torque values using a mathematical equation. After completion of the development and construction of the prototype, the functional and resistance evaluations were conducted and followed by dynamic tests for the validation of the torque meter. During traction tests, it was performed evaluations on two surfaces (concrete and firm soil), three gears, up to eight drawbar pull and evaluations with the wheel assist drive on and off. The results for the validation of the equipment were statistically analyzed using regression equations, highlighting the linearity ...